Development of an assessment instrument to evaluate the concepts of chemical equilibrium at macroscopic, sub-microscopic, and symbolic representation levels using the rasch model - Difa Aulia Putri Rizal; Faizah Qurrata Aini (Jurnal Pijar Mipa, 2023)
This study aims to develop a test instrument that can be used to evaluate the concept of chemical equilibrium at the macroscopic, submicroscopic, and symbolic levels of high school students who are declared valid, reliable, have a difficulty index, and have good item discrimination. This study was designed using the Rasch development model, which Wei has modified with ten research stages. The results of the research to test content validity were analyzed through the minifacets program with five validators consisting of four chemistry lecturers at Padang State University and one teacher at high school SMAN 3 Padang, obtaining fit analysis results seen from the exact agreement value of 89.1%, which is very close to the expected agreement value of 89.7%. The test results on 30 students of SMAN 3 Padang who were analyzed through the ministep program showed valid results for all items because they met the criteria for the MNSQ, ZSTD, and Pt Mean Corr outfit scores. The reliability value obtained for the item is 0.74, which meets the sufficient criteria, and Cronbach's alpha reliability value is 0.74, which meets the good criteria. All question items also do not have DIF based on gender. The analyzed index of difficulty and discriminating power fulfilled the good criteria with the classification of easy, medium, and difficult items.